Saturation mutagenesis reveals manifold determinants of exon definition - Ke, Shengdong; Anquetil, Vincent; Zamalloa, Jorge Rojas; Maity, Alisha; Yang, Anthony; Arias, Mauricio A.; Kalachikov, Sergey; Russo, James J.; Ju, Jingyue; Chasin, Lawrence A. (Genome Research, 2018)
To illuminate the extent and roles of exonic sequences in the splicing of human RNA transcripts, we conducted saturation mutagenesis of a 51-nt internal exon in a three-exon minigene. All possible single and tandem dinucleotide substitutions were surveyed. Using high-throughput genetics, 5560 minigene molecules were assayed for splicing in human HEK293 cells. Up to 70% of mutations produced substantial (greater than twofold) phenotypes of either increased or decreased splicing. Of all predicted secondary structural elements, only a single 15-nt stem–loop showed a strong correlation with splicing, acting negatively. The in vitro formation of exon-protein complexes between the mutant molecules and proteins associated with spliceosome formation (U2AF35, U2AF65, U1A, and U1-70K) correlated with splicing efficiencies, suggesting exon definition as the step affected by most mutations. The measured relative binding affinities of dozens of human RNA binding protein domains as reported in the CISBP-RNA database were found to correlate either positively or negatively with splicing efficiency, more than could fit on the 51-nt test exon simultaneously. The large number of these functional protein binding correlations point to a dynamic and heterogeneous population of pre-mRNA molecules, each responding to a particular collection of binding proteins.